Investigating the Compressive Strength Properties of Concrete Using Some Common Ghanaian Ordinary Portland Cements (International Journal of Technology and Management Research, 2021)
In a general sense, concrete is made of cementitious material, aggregates and water but the mix productivity is one issues that affect the amount of strength concrete developed. The concrete mix productivity is a direct function of the amount and quality of the cementitious material. The commonest cementitious material used for concrete in Ghana like other countries in the world is the Ordinary Portland Cement. The research sort to investigate the compressive strength properties of concrete made from some common Ghanaian Ordinary Portland Cement brands mostly used in the countries construction industries. The research strategy adopted was experimental. The research was a cross –sectional studies and used laboratory tests to get information on all cements. Cement grade 42.5N, 42.5R and 32.5R were used. A total of one – hundred and eight (108) concrete cubes were made from nine different brands of Ordinary Portland Cement with a mix design of 1:2:4. No admixtures were used in the mix. It was established that, Ordinary Portland Cement Brand E of grade 42.5R has the highest compressive strength after 28 days. Some of the cement brand with grade 32.5R developed better strength than that of grade 42.5R. Based on the experiment conducted, it can be concluded that for the C15 (1:2:4) and C20 compressive strength as per IS 456:2000, Ordinary Portland Cement Brand E and G of grade 42.5R and Ordinary Portland Cement Brand H and J of grade of 32.5R satisfactory meets the requirement. It implies that some of the Ghanaians Portland Cement developed a satisfactory compressive strength and meets the minimum strength attainment after 28 days’ which is 15 N/mm2. Based on the result, it is recommended that Ordinary Portland Cement Brand E of grade 42.5R should be used for most concrete production and Ordinary Portland Cement Brand J of grade 32.5R can also be used for concrete work in the absence of E 42.5R. Citation: Akorli, K. S., Danso, K., Ayarkwa, J. and Acheampong, A. (2021). Investigating the Compressive Strength Properties of Concrete Using Some Common Ghanaian Ordinary Portland Cements.International Journal of Technology and Management Research (IJTMR), Vol. 6 (1): Pp.154-166.[Received: March 13, 2021Accepted: September 1, 2021
Keywords: ordinary portland cement; concrete; compressive strength; rate of strength; age